Promotion of ethical principles in provision of medication therapy management services - Sarah E. Kelling; Julie M. Aultman (University of Minnesota Libraries Publishing, 2014)
As pharmacists move toward more patient-centered care through medication therapy management (MTM), important issues and conflicts may arise within the therapeutic relationship, requiring pharmacists to use ethical knowledge and skills toward conflict-resolution. The purpose of this paper is to explore practical strategies that pharmacists and other champions of MTM may utilize to support the ethical principles of autonomy, veracity, nonmaleficence, beneficence, and justice, along with an ethic of care during the provision of MTM services. With a deeper understanding of ethical principles and the Code of Ethics for Pharmacists, pharmacists may be more prepared to make difficult ethical decisions, and ultimately, guide better patient care.   Type: Idea Paper